Litiase biliar em porca - Monteiro Wilwerth , Leon (Revista Ceres, 1939)
The author describes a rare case of biliary lithiasis in swine, Post-mortem examination of a Poland-China hog revealed 6 large calculi weighing 248.700, 245.300, 203.150, 127.200, 102.175 and 50.50 grms. respectively, or a total of 976.575 grams. Qualitative analysis of the stones showed the presence of calcium bilirubinate and cholesterin. Necrosis and regressive hepatic lesions had produced internal hemorrhage which caused the death of the animal.